Pengaruh Penggunaan Alat Peraga dalam Pembelajaran IPA SMP Terhadap Hasil Belajar Siswa - Ines Coria Vera; Monica Prima Sari (Natural Science, 2022)
This study aims to see the effect of using science teaching aids in learning to improve student's learning outcomes. This study uses the ex-post facto method with effect size analysis. The population of this study is all reputable and indexed articles related to the use of teaching aids in Integrated Science learning at the SMP/MTS level. The sample in this study was 11 articles accredited by SINTA and indexed by SCOPUS. The criteria for the articles used are articles that discuss the effect of using teaching aids in Integrated Science learning at the SMP/MTS level, published in 2018-2021. The results of this study indicate that the use of science teaching aids in learning can improve student’s learning outcomes.